Twelve month follow‐up of a contraceptive implant outreach service in rural Papua New Guinea. (April 2017) - Gupta, Sarika; Mola, Glen; Ramsay, Philippa; Jenkins, Greg; Stein, Wendy; Bolnga, John; Black, Kirsten
Abstract : Background: Poor access to contraception contributes to persistently high maternal mortality rates in Papua New Guinea (PNG). Since 2012 contraceptive implants have been provided to women in rural areas of PNG through outreach services but follow‐up data in these communities on continuation and acceptability is lacking. Objective: To gain insight into women's experience with contraceptive implants by assessing the acceptability, satisfaction, 12 month continuation rates and efficacy of contraceptive implants among women in rural PNG. Material and methods: We undertook a cross‐sectional survey of women in two rural provinces who had received a contraceptive implant at least 12 months prior using a structured questionnaire. We sought information on device continuation rates, satisfaction scores, side effects and failure rates. Results: Of the 860 women surveyed, 97% ( n = 836) still had the device in situ after 12 months and 92% ( n = 793) were very happy with it. Seventy‐six percent of women ( n = 654) reported no side effects. Irregular bleeding was the most commonly reported side effect ( n = 178, 20.6%) but only 7% ( n = 13) said the bleeding was bothersome. Documented failure rates were 0.8% although pregnancy at the time of insertion could not be excluded in any of these cases. Conclusion: Twelve month implant follow‐up data in this study showed high continuation rates and high levels of satisfaction among a rural population in PNG. Implants have the potential to lower maternal morbidity and mortality and simultaneously address the unmet need for contraception in these communities.